Correspondence from Miriko Nagahama to Betty Salzman, March 2, 1943 - Miriko Nagahama::::::author:::
Personal letter discusses Nagahama's shorthand and drafting classes; Salzman's promotion to instrument tester [at Lockheed]; her own and Salzman's saxophone playing; Hideo [Watanabe's?] employment as business manager in the "Free Press" (her quotes) office; and rationing at Manzanar. She also expresses sorrow at the loss the prior week of 177 "former Bainbridge Island people" who had been removed to "Hunt Relocation Center in Minidoka, Idaho" mentioning that they had petitioned to "evacuate to the Idaho center right after the riot when there was so much tension because they wanted to be with the people from up north where they had come from." She further discusses her surprise that people had been brought to Manzanar from Bainbridge Island in the first place.